Penilaian Kinerja dan Penyusunan AKNOP Embung di Provinsi Bali - Irma Suryanti; Putu Indah Dianti Putri; Made Widya Jayantari (Jurnal Ilmiah Telsinas, 2022)
Performance assessment and preparation of AKNOP (operation and maintenance costs) were carried out on 13 reservoirs in the province of Bali, including Embung Badeg, Embung Batudawa, Embung Baturinggit, Embung Besakih, Embung Bukit, Embung Datah I, Embung Datah II, Embung Dukuh, Embung Muntig, Embung Seraya Timur, Embung Seraya, Embung Telung Buana, and Embung Untalan located in Karangasem Regency. The purpose of this study is to evaluate the reservoir performance against the specified assessment aspects and to obtain the planned operating and maintenance costs for the reservoir facilities and infrastructure based on the damage criteria. The evaluation of the operation performance and maintenance of the reservoir refers to the Circular Letter of the General Director of Water Resources, Ministry of Public Works and Housing. Meanwhile, the AKNOP value is calculated from the total of multiplication volume, frequency, and unit price of work for each reservoir operation and maintenance activity. The reservoir performance evaluation is based on four criteria, physical performance, operating and service performance, security and environmental system performance, and institutional performance. From the study, the result shows that 13 reservoirs' performances are in adequate condition. The operation and maintenance can be done by routine and periodic maintenance activities based on operating and maintenance cost plans. This activity is expected to reduce reservoir damage.